Eksplorasi Etnomatematika pada Tari Lenggang Nyai Betawi dalam Aktivitas Fundamental Matematis Bishop - Rahayu, Nabillah Pangesti; Hartati, Leny; Kasyadi, Soeparlan (Innovative: Journal Of Social Science Research, 2024)
The purpose of this study is to explore and describe the mathematical concepts contained in the Betawi lenggang nyai dance in Bishop's fundamental mathematical activities. The research method used is ethnomathematics research through a qualitative approach, with the data technique used being the Spradley model analysis technique. The research instruments are in the form of observation guidelines and interview guidelines. The object of this study is the lenggang nyai dance. Based on the research results, there are basic mathematical concepts in the lenggang nyai dance including the concept of flat shapes such as squares and triangles, number patterns such as arithmetic patterns, angles such as acute and obtuse angles, rotations and degrees such as full 360 degree rotations and half 180 degree rotations, lines such as diagonal lines and curved lines, and transformation geometry such as translation, rotation, reflection, and dilation, in addition there are also Bishop mathematical aspects with six activities, namely counting activities such as the number of dancers, location determination activities such as determining the direction and position of the dancers, measuring activities such as measuring the size of angles in movements, designing activities such as making floor patterns, playing activities such as applying strategies and rules to the lenggang nyai dance, and explaining activities such as explaining the history, philosophy, meaning, and development of the lenggang nyai dance. So it can be concluded that ethnomathematics exploration can be found in the lenggang nyai dance.